Successful salvage treatment of refractory recurrence of maxillary sinus carcinoma using image-guided high-dose-rate interstitial brachytherapy - Zhang, Yin; Wu, Ning; Zhao, Zhipeng; Chen, Qianqian; Cheng, Guanghui (Journal of Contemporary Brachytherapy, 2018)
This case report illustrates a treatment effect of image-guided high-dose-rate (HDR) interstitial brachytherapy for refractory recurrence of maxillary sinus carcinoma. A 61-year-old male was previously admitted to another hospital and received surgery because of left maxillary sinus squamous cell carcinoma (SCC) 6 years ago. Tumor regrowth was noted 2 years after the initial radical surgery. The patient accepted local excision again for the recurrence, followed by external beam radiotherapy. Despite salvage treatment with surgery and external irradiation, the lesion expanded as 4.8 × 4.4 × 4.0 cm3. Because the patient refused palliative resection, we recommended technique of image-guided HDR interstitial brachytherapy. The total doses of 42 Gy in 12 fractions were delivered to the whole recurrent tumor. Removal of the recurrent tumor was securely achieved by HDR interstitial brachytherapy, guided with ultrasound. The refractory tumor in the patient healed uneventfully after HDR interstitial brachytherapy without recurrence during 8 months of follow-up. This case is remarkable because the patient experienced complete remission by a safe and practicable method with image-guided HDR interstitial brachytherapy.